Role of Emx2 in the development of the reciprocal connectivity between cortex and thalamus. - López-Bendito, G; Chan, C; Mallamaci, A; Parnavelas, J; Molnár, Z (2002)
Emx2 knockout mice appear to show a shift in the areal identity in the cerebral cortex , which is matched with altered distribution of thalamocortical projections (Bishop et al. [2000] Science 288:344-349; Mallamaci et al. [2000] Nat Neurosci. 3:679-686) [corrected]. We have examined the early establishment of these projections to understand how the altered Emx2 expression results in changes in their cortical targeting. We used carbocyanine dye tracing to visualize thalamocortical and corticofugal projections as well as immunohistochemistry for L1 and TAG-1, respective markers of the two axonal systems, in wild-type, heterozygote, and null mutant for Emx2 at embryonic (E) ages ranging from E13.5 to E18.5. These tracing studies demonstrated that, in Emx2 knockout mice, a large proportion of early thalamocortical projections were misrouted at the border between the diencephalon and telencephalon. This abnormality was associated with displaced connectivity of the internal capsule cells at the diencephalic-telencephalic junction. Interestingly, most of the aberrant thalamic projections compensated for the ventral entry to the telencephalon and still ascended to the cortex. Although this early targeting abnormality is associated with the altered Emx2 expression pattern in the cortex, it most probably occurs independently from it, and is related to earlier guidance defects at the diencephalic-telencephalic boundary. These defects might result in the altered and delayed arrival of thalamic projections to the cortex and, thus, contribute to the shifted thalamocortical matching previously observed in the Emx2 knockout mice.